#TITLE_ALTERNATIVE# - DANY VARIANDY (NIM: 25112016); pembimbing: Dr.Ir. Kosasih Prijatna, M.Sc. ; Dr. techn. Dudy D, ERFAN
Superconducting Gravimeter (SG) is a precise tool to measure the gravity up the fraction of NanoGal. SG station located at Badan Informasi Spasial in Cibinong is the only station located around the equator. This research aims to analyze the spectral components of SG data and to find the main component, i.e. the earth tides. The data used in this research are SG data at Cibinong station for 1.5 years and supporting data, namely air pressure at the station. The pre-processing step is done to determine the calibration factor and to remove the noise, such as earthquake signals, outlier, offset, data gap, and the decreasing value of data due to the liquid helium filling. The modelling to separate each component was done with using supporting data, such as polar motion, ocean loading, and the height variation of ground water level. The results of spectral analysis show that almost all components are dominant in long period frequency. While the dominant components at short period frequency, especially diurnal and semi-diurnal, are ocean loading, hydrology, and the effect of air pressure. The residuals are the earth tide components, whose value varies from -50 until -350 μGal, and the mean value is 108.6667 Ã‚Â± 15.1085 μGal